2015
DOI: 10.3389/fgene.2015.00298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single nucleotide polymorphism markers associated with bacterial cold water disease resistance and spleen size in rainbow trout

Abstract: Bacterial cold water disease (BCWD) is one of the frequent causes of elevated mortality in salmonid aquaculture. Previously, we identified and validated microsatellites on chromosome Omy19 associated with QTL (quantitative trait loci) for BCWD resistance and spleen size in rainbow trout. Recently, SNPs (single nucleotide polymorphism) have become the markers of choice for genetic analyses in rainbow trout as they are highly abundant, cost-effective and are amenable for high throughput genotyping. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 24 publications
5
48
1
Order By: Relevance
“…) and cortisol response (Liu et al . ) in rainbow trout, and thermal tolerance and growth in Oncorhynchus nerka , the sockeye salmon (Larson et al . ).…”
Section: Applications Of Rad Sequencing In Aquaculturementioning
confidence: 99%
“…) and cortisol response (Liu et al . ) in rainbow trout, and thermal tolerance and growth in Oncorhynchus nerka , the sockeye salmon (Larson et al . ).…”
Section: Applications Of Rad Sequencing In Aquaculturementioning
confidence: 99%
“…Several genome-wide association studies (GWAS) that match genetic variants, with or without pedigree records, with the observed phenotype have identified significant loci associated with economically important traits in livestock (Kadarmideen, 2014; Sharma et al, 2015). The aquaculture research community is following this trend, and interesting examples are available for growth and disease resistance traits in Atlantic Salmon (e.g., Correa et al, 2015; Gutierrez et al, 2015), rainbow trout (e.g., Kocmarek et al, 2015; Liu et al, 2015b; Palti et al, 2015b), and catfish (e.g., Geng et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…It has also facilitated the identification of individual loci or regions of the genome directly under natural selection. "Top-down" approaches, such as genome-wide association studies and quantitative trait locus mapping, enable the discovery of regions of the genome associated with ecologically important traits (e.g., Jones et al 2012;Küpper et al 2015;Liu et al 2015;Pavey et al 2015;Comeault et al 2016). Alternatively, using "bottom-up" (or genome-scanning) approaches, it is possible to statistically detect loci under divergent selection between populations, and to use this information to identify candidate phenotypes previously not known to be under selection (Turner et al 2010;Fumagalli et al 2015;Kardos et al 2015;Manel et al 2016).…”
mentioning
confidence: 99%